The essential effect of mTORC1-dependent lipophagy in non-alcoholic fatty liver disease - Tan, Xiangyun; Huang, Xinyu; Lu, Zhuhang; Chen, Liang; Hu, Junjie; Tian, Xianxiang; Qiu, Zhenpeng (Frontiers in Pharmacology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a chronic progressive liver disease with increasing prevalence. Lipophagy is a type of programmed cell death that plays an essential role in maintaining the body's balance of fatty acid metabolism. However, the livers of NAFLD patients are abnormally dysregulated in lipophagy. mTORC1 is a critical negative regulator of lipophagy, which has been confirmed to participate in the process of lipophagy through various complex mechanisms.Therefore, targeting mTORC1 to restore failed autophagy may be an effective therapeutic strategy for NAFLD. This article reviews the main pathways through which mTORC1 participates in the formation of lipophagy and the intervention effect of mTORC1-regulated lipophagy in NAFLD, providing new therapeutic strategies for the prevention and treatment of NAFLD in the future.